PERANCANGAN APLIKASI BANK SAMPAH “SAMPAHQU” BERBASIS MOBILE DI TANGERANG SELATAN MENGGUNAKAN RAPID APPLICATION DEVELOPMENT - Hery Hery; Helena Juliana Kristina; Eric Jobiliong; Agustina Christiani (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
Currently, household waste management has been managed by a waste bank so that the existing daily waste is collected and sorted to be recycled to make the environment better and less pollution-free. In carrying out its activities, the Garbage Bank in South Tangerang City experienced problems starting from the process of depositing waste from customers, the process of recording transactions and reporting transactions that occurred, modifying so that customer data collection, types of waste, and existing reports were still not well organized and there were no media. Communication can be used between the waste bank and waste bank customers. This research will design a waste bank information system for waste management in South Tangerang from the existing problems. The Rapid Application Development (RAD) methodology with the prototyping method is used in designing a mobile-based integrated waste bank application. The proposed system uses UML (Unified Modeling Language) modeling. The results of this study are an integrated waste bank application that can make a good contribution, namely helping the community to deposit their household waste and assisting waste bank managers in making effective and efficient recording and reporting